Quality of life among people with mental illness attending a psychiatric outpatient clinic in Ethiopia: a structural equation model - Alemu, Wondale Getinet; Mwanri, Lillian; Due, Clemence; Azale, Telake; Ziersch, Anna (Frontiers in Psychiatry, 2024)
Background: Mental illness is one of the most severe, chronic, and disabling public health problems that affects patients' Quality of life (QoL). Improving the QoL for people with mental illness is one of the most critical steps in stopping disease progression and avoiding complications of mental illness. Therefore, we aimed to assess the QoL and its determinants in patients with mental illness in outpatient clinics in Northwest Ethiopia in 2023. related factors, drug use factors, and clinical factors, directly and indirectly affected QoL through the mediator variables of physical health domains, psychological health domains, social relation health domains, and environmental health domains. In order to improve the QoL of people with mental illnesses, we recommend that emphasis be given to addressing the QoL of those with mental illness, including the development of policy and practice responses that address the above identified factors.